PENGARUH KOMPENSASI DAN KOMUNIKASI TERHADAP KEPUASAN KERJA PERAWAT HONORER INSTALASI GAWAT DARURAT (IGD) DAN RAWAT INAP RUMAH SAKIT UMUM DAERAH Z DI KABUPATEN BANDUNG BARAT - Adelia Fitriani Agustin; R. M. Juddy Prabowo (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2024)
In 2020-2022 the number of honorary emergency room and inpatient nurses from Regional General Hospital Z in West Bandung Regency who left was not comparable to the nurses who came in, especially in 2020. Based on information provided by the head of nursing at RSUD Z, a number of nurses with sufficient competence both were offered more promising jobs, prompting some nurses to move voluntarily. The aim of the research is to examine the influence of compensation and communication simultaneously and partially on the job satisfaction of honorary emergency room and inpatient nurses at RSUD Z in West Bandung Regency. This research applies quantitative methodology. The method for collecting data was through a questionnaire with 33 honorary nurses as respondents according to the research characteristics with research measuring scale using semantic differential. The results of the study show that both compensation and communication influence the job satisfaction of honorary emergency room and inpatient nurses at RSUD Z in West Bandung Regency. In addition, both correlate with job satisfaction simultaneously.